Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1108/pijpsm-06-2018-0078
|View full text |Cite
|
Sign up to set email alerts
|

Patrol career interest and perceptions of barriers among African-American criminal justice students

Abstract: Purpose-The purpose of this paper is to evaluate whether black and African-American criminal justice students perceive barriers to a police patrol career differently than white students, and whether the perceptions of these barriers impact desire to enter a police patrol career. Design/methodology/approach-The current inquiry uses a self-administered survey of over 630 undergraduate students in criminal justice classes across five public universities. Findings-Findings suggest that African-American students di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Several other demographic variables have been shown to influence both perceptions of barriers to entering a police career and patrol career interest (Rossler et al., 2019). As such, we include a series of control variables for race (i.e., Black, Latino, Other race), with White students serving as the reference category.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several other demographic variables have been shown to influence both perceptions of barriers to entering a police career and patrol career interest (Rossler et al., 2019). As such, we include a series of control variables for race (i.e., Black, Latino, Other race), with White students serving as the reference category.…”
Section: Methodsmentioning
confidence: 99%
“…One suggestion is to bring in a critical mass of female recruits. Based on the results of Aiello (2018), that when the physical expectations were explicitly stated on recruitment materials, physicality was not a significant barrier for women interested in a policing career. Future research should replicate these findings to see if explicitly stating academy experiences such as tasering and pepper spraying recruits (or explicitly stating recruits will not be exposed to tasering and Oleoresin Capsicum spray) and hand combat and physical fighting expectations will reduce their likelihood of being a barrier to potential female recruits.…”
Section: Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While this study serves as an important first step in assessing perceptions on drug disqualifiers by both potential police applicants and those hiring them, there is still a great deal of work that can be done moving forward. Future research should use multivariate models to examine different demographic factors that may influence the perspectives on drugs and other police career issues (see Rossler et al, 2019, 2020), as well as find ways to survey samples more representative of police applicants. Furthermore, it would also be valuable to examine the perspectives of both chiefs and students in other states to better understand the generalizability of these findings and the potential for similar or different rule change recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, students majoring and double majoring in law enforcement and criminal justice are significantly less likely to perceive that officers engage in police misconduct than students majoring outside of law enforcement and criminal justice (Sethuraju et al, 2017). Rossler, Scheer, and Suttmoeller also found that CJ majors have greater overall respect for the police (Rossler et al, 2018). This study evaluated black and African-American criminal justice students to see if their perceptions of barriers to a police patrol career differ from white students, in addition to seeing if their perceptions of these barriers impact their desire to enter a police patrol career.…”
Section: Indirect Educational Experiences and Its Relation To Collegementioning
confidence: 97%